Tendon-Specific Dicer Deficient Mice Exhibit Hypoplastic Tendon Through the Downregulation of Tendon-Related Genes and MicroRNAs - Omoto, Takenori; Yimiti, Dilimulati; Sanada, Yohei; Toriyama, Minoru; Ding, Chenyang; Hayashi, Yuta; Ikuta, Yasunari; Nakasa, Tomoyuki; Ishikawa, Masakazu; Sano, Masayuki; Lee, Minjung; Akimoto, Takayuki; et al. (Frontiers in Cell and Developmental Biology, 2022)
Tendon is a fibrous connective tissue, that is, transmitting the forces that permit body movement. However, tendon/ligament biology is still not fully understood and especially, the role of miRNAs in tendon/ligament is sparse and uncharacterized in in vivo models. The objectives of this study were to address the function of DICER using mice with tendon/ligament-specific deletion of Dicer (Dicer conditional knockout; cKO), and to identify key miRNAs in tendon/ligament. Dicer cKO mice exhibited hypoplastic tendons through structurally abnormal collagen fibrils with downregulation of tendon-related genes. The fragility of tendon did not significantly affect the tensile strength of tendon in Dicer cKO mice, but they showed larger dorsiflexion angle in gait compared with Control mice. We identified two miRNAs, miR-135a and miR-1247, which were highly expressed in the Achilles tendon of Control mice and were downregulated in the Achilles tendon of Dicer cKO mice compared with Control mice. miR-135a mimic increased the expression of tendon-related genes in injured Achilles tendon-derived fibroblasts. In this study, Dicer cKO mice exhibited immature tendons in which collagen fibrils have small diameter with the downregulation of tendon-related genes such as transcriptional factor, extracellular matrix, and miRNAs. Thus, DICER plays an important role in tendon maturation, and miR-135a may have the potential to become key miRNA for tendon maturation and healing.